Long-term Stochastic Forecasting of the Nuclear Energy Global Market - Vladimir Kharitonov; Uliana Kurelchuk; Sergey Masterov (Foresight and STI Governance, 2015)
This article looks at the problem of devising a long-term developmental forecast of the nuclear energy market and the possibility of studying certain sections of the market. Bearing in mind the current state of the market and associated industries, it is particularly important to have a scientific approach to developing statistical forecasting instruments and methods with assessments of the dispersion of forecasts. is particularly important. The authors are the first to have developed and applied a probabilistic forecasting method for severala number of market indicators reflecting the physical size of the global nuclear energy industry for the period up to 2035, and in particular: the number and electrical capacity of reactors in service or taken out of service, and the demand for natural and enriched uranium and enrichment services. The forecasting relies on stochastic modelling of nuclear power plant (NPP) life cycles and operating characteristics, open nuclear fuel cycle parameters, and energy policy in corresponding regions around the world. Unlike scenario approaches, this model makes it possible to obtain probabilistic distributions of these characteristics, which is important when assessing the economic risks of various participants in the global nuclear energy market.The results obtained from the long-term forecast of NPP capacity dynamics for the world as a whole and for the largest regions of the planet are consistent with the scenarios of the World Nuclear Association (WNA) and the International Atomic Energy Agency (IAEA). These scenarios are developed on the basis of data provided by members of these organizsations, which confirms the reliability of the frequency distribution model used for key stages of the reactor life cycle. The authors have modelled the market’s probable new NPP construction volumes and NPP decommissioning volumes over the next 15 years in Russia, globally, and in certain world regions. The paper also presents an analysis of the likely capacity of the new Russian-made NPP construction market globally and its share of the global services map in this field up to 2030.